Confrontations aux traces de son activité - Béatrice Cahour; Christian Licoppe (Revue d'anthropologie des connaissances)
In everyday life, situations involving confrontation with the traces of our activities are becoming commonplace, through technologies that objectivate and make available our experiences and conduct. Our "informational ecologies" are increasingly reflexive, which elicits performative effects and a mediated return to self, or a dialectic between subject and object which produces transformations. This is the case, for example, with diabetic diaries, through which patients develop a mastery of their pathology, or with a new automatic epileptic seizure detection device that leads different actors to confront their points of view on the relevant experiential data and inscriptions. In addition, self-confrontation, or confrontation with video/audio/written traces of one's own activity, is a powerful reflexive device, this time set up by the researcher. The observable video traces of the lived activity mediate experiences, to help subjects to remember and to describe in detail the activity carried out or to re-elaborate it, and thus to develop knowledge to act and knowledge about the action. There are two types of objectives here: (1) to describe subjet’s experiences in phenomenological detail in order to gain an elaborate understanding of the activity at hand (e.g. musician-composer, rugby referees); (2) to provoke an analytical and collective elaboration and the emergence of controversies for the development of skills and activity (e.g. construction workers).